2014
DOI: 10.1002/term.1890
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial shock-wave therapy improves ventricular function in a porcine model of ischaemic heart disease

Abstract: Previously we have shown that epicardial shock-wave therapy improves left ventricular ejection fraction (LVEF) in a rat model of myocardial infarction. In the present experiments we aimed to address the safety and efficacy of epicardial shock-wave therapy in a preclinical large animal model and to further evaluate mechanisms of action of this novel therapy. Four weeks after left anterior descending (LAD) artery ligation in pigs, the animals underwent re-thoracotomy with (shock-wave group, n = 6) or without (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
(37 reference statements)
1
30
1
Order By: Relevance
“…Vasodilation and angiogenesis of the corpus cavernosum are proposed mechanisms of LI‐SWT on erectile function recovery. Shock waves induce shear stress, which induces various cytokine releases, such as NO and VEGF . Shock wave forms NO non‐enzymatically, and enhances the expression of VEGF and its receptor Flt‐1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasodilation and angiogenesis of the corpus cavernosum are proposed mechanisms of LI‐SWT on erectile function recovery. Shock waves induce shear stress, which induces various cytokine releases, such as NO and VEGF . Shock wave forms NO non‐enzymatically, and enhances the expression of VEGF and its receptor Flt‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…Shock waves induce shear stress, which induces various cytokine releases, such as NO and VEGF. [13][14][15][16] Shock wave forms NO non-enzymatically, and enhances the expression of VEGF and its receptor Flt-1. 13,15 Wang et al reported that shock wave therapy produced a significantly higher number of neovessels and angiogenesis-related markers including endothelial NO synthase, VEGF and proliferating cell nuclear antigen than the control without shock wave treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the applicator's membrane is 4.5 cm and 300 impulses were delivered to the ischaemic area with an energy flux density of 0.1 mJ/mm 2 at a frequency of 5 Hz. The rationale for the treatment parameters is experience from previous studies (Tepekoylu et al ., ; Holfeld et al ., ,b). No adverse effects have been observed at these energy levels.…”
Section: Methodsmentioning
confidence: 99%
“…First clinical applications resulted in a relief of angina symptoms in patients suffering from coronary heart disease; induction of angiogenesis at the border zone of the infarcted area and subsequent contractile improvement of hibernating myocardium were described. Although numerous effects, including increased vascular endothelial growth factor (VEGF) and nitric oxide (NO) production, enhanced progenitor cell recruitment and induction of endothelial cell proliferation have been described, the underlying mechanisms remain largely unknown (Aicher et al, 2006;Tepekoylu et al, 2013;Holfeld et al, 2014b;Weihs et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that CSWT improves LV function and inhibits LV remodeling [26] by enhancing angiogenesis [11,[27][28][29], attenuating the inflammatory response [9,30,31] and reducing oxidative stress [9] in the ischemic heart in vivo. However, the role of the CSWT effect on cardiomyocyte apoptosis after AMI remains to be elucidated.…”
Section: Mechanisms Of the Suppression Effects Of Cswt On Cardiomyocymentioning
confidence: 99%